Resource needs screening and matching at an academic oncology center: RESOURCE preliminary results. Issue 28 (1st October 2022) - McCleary, Nadine Jackson; Haakenstad, Ellana K; Neville, Bridget A.; Weitzner, Rachel; Zhang, Sunyi; Manni, Michael; Cleveland, Jessica; Toffler, Deborah H; Wallace, Julie P; Hassett, Michael J.
Abstract : 178 Background: The social determinants of health contribute to patient (pt) health status throughout the cancer care continuum. Here we describe preliminary results of RESOURCE, a pragmatic intervention to ID and intervene on pt resource needs at an academic oncology center. RESOURCE is an EHR-integrated questionnaire (qst), given when establishing oncology care, that IDs the following needs: transportation; financial, food, & housing security; cost of care; education & employment; and caregiving burden. Pts from an HUP population or reporting resource needs on the cancer center's intake qst are screened with RESOURCE. Those randomized to the intervention reporting a resource need receive an EHR-mediated referral to internal resource specialist and financial assistance teams. Methods: All adult cancer pts may complete the EHR-integrated intake qst. We compared historic rates of reported vulnerability from the intake qst with resource needs reported in RESOURCE. Intake qst data from 6/2015 – 4/2022 included 21, 343 respondents with data on financial security, social isolation, health literacy, and health numeracy. RESOURCE data from 6/2021 – 6/2022 on the domains above included 75 respondents (125 will be accrued in total; no conditions will end accrual early). The intake qst is available for all adult cancer pts (response rate 24%; RESOURCE response rate of 87%). and The following were compared with χ 2 tests: the demographic profile of each pt population; and the proportion of respondents with any one need ID'd by RESOURCE vs the intake qst. These preliminary results allow us to determine if we may prepare to scale RESOURCE upon the study's completion. Results: The enriched pt population of RESOURCE means that there is a statistically significant difference in demographics between the general pt population responding to the intake qst and the RESOURCE pts responding to the RESOURCE by each category (p-values < 0.01). A higher proportion of pts identified a need on the intake qst (61%) than on RESOURCE (41%). RESOURCE pts most commonly reported the following needs: paying utility bills (24%), food security (20%), and cost of care (19%). Conclusions: While a larger proportion of pts reported a resource need on the intake qst, the RESOURCE qst had a far superior response rate; this discrepancy makes it difficult to determine which qst is better at determining resource needs. The RESOURCE qst allows us to see the type of need in greater detail. Collecting this data systematically allows us to quantify the resource needs of our pts so we can provide adequate support staff and resources. Any resource need RESOURCE, # (%) Any resource need intake qst, # (%) P-Value Overall 31 (41) 13, 151 (63) < 0.001 RESOURCE Needs reported, # (%) Transportation 9 (12) Food security 15 (20) Paying utility bills 18 (24) Housing security 13 (17) Cost of care 14 (19) Education & employment 8 (11) Caregiving 7 (9)